Representasi Makna Keikhlasan Pada Series “ Layangan Putus ” - Aisyah, Yola Hayatul; SM, Anis Endang; Maryaningsih, Maryaningsih (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research was conducted to analyze the representation of sincerity shown by women in the drama series